Review of digital image correlation application to large-scale composite structure testing - Janeliukstis, R.; Chen, X.
This study reviews the recent progress in the application of digital image correlation (DIC)to testing composite structures with an order of size magnitude of meters. The DIC technique has gained wide popularity in materials and structural testing due to the merit of being full-field and non-contact compared to conventional point-wise measurement techniques. This study focuses on the DIC application to large-scale composite structure testing. Experimental setup requirements, measurement capabilities, and the associated challenges are thoroughly reviewed and analyzed. Typical applications found in the literature are from wind energy and aerospace sectors for displacement and strain measurements under static loading and operational modal analysis in dynamic structural tests. The remaining challenges along with their possible solutions are discussed and summarized in this work to shed light on future research needs on testing large-scale composite structures using the DIC technique.
Keywords: DIGITAL IMAGE CORRELATION; COMPOSITE STRUCTURES; STRUCTURAL TESTING; OPERATIONAL MODAL ANALYSIS; AEROSPACE STRUCTURES; WIND TURBINE BLADES